A comparative literary study of the prosodic systems of English and Arabic poetry - Elyasa, Yasir M (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study investigates the similarities and differences between the prosodic systems of English and Arabic poetry. It is qualitative research on the two systems, where the methods of representation are explained, compared, and contrasted, with examples of words and lines from both languages’ poetry. It supposes that music, as a common ground for the poetry of both languages, has given them the essential elements of having to do with the beat and rhythm, though these terms are slightly different in music. This is added to the fact that both are rhythmic languages, affected by the factor of rhythm as a common feature between them. Furthermore, the study attempts to prove that it is possible to have some examples of Arabic poetry represented through the English prosodic system and vice versa. This showed that there is much similarity between the two systems in the practical sense of depending on the vowels as fundamental to the existence and representation of syllables. The differences between the two prosodic systems were found in the significance of the level of the beats and the representation of consonants and long vowels.